The Sharia Pawnshops and Its Role for Community Resilience in the days of Covid-19 Pandemic: Evidence from Indonesia and Malaysia - Andi Bahri S; Yusuf Hardiansyah (Tazkia Islamic Finance and Business Review, 2022)
In this modern era especially during pandemic (Covid-19), we found that most of country in the world facing economic crisis include Indonesia and Malaysia. One of institution which was growing in both country is Pawnshop and it’s develop and promoting the Islamic economy especially during pandemic (Covid-19). One of the alternative for this economic crisis issue especially during pandemic is doing Rahn transaction to get speedy cash and at the same time. This study aims to analyze the differences between pawnshop in Indonesia and Malaysia. This study used qualitative description method with an approach to library research (literature review). The qualitative method is used to analyze the instrument or products which provided by pawnshops. Result of this study are both pawnshop have a goal and want to become the most valuable financial company by following and or meet the community needs. Indonesia’s pawnshop and Malaysia’s pawnshop provide different product. Malaysia’s pawnshop product just serviced only gold, but Indonesia’s pawnshop more various such as gold, hajj installment, and vehicle mortgage/credit and etc. Keywords: Sharia Pawnshop, Pawnshop Product, Rahn, Community Resilience, Covid-19.